2023
DOI: 10.7759/cureus.33825
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between Use of Topical Honey and Edinburgh University’s Solution of Lime (EUSOL) Dressing in Necrotizing Fascitis Wounds

Abstract: IntroductionNecrotizing soft tissue infection is potentially life-threatening and involves subcutaneous fascial planes, later involving overlying skin and, eventually, underlying muscles. Early diagnosis and prompt treatment are necessary for this disease's management to avoid significant morbidity and fatality. After resuscitation and optimization, early surgical debridement is followed by serials of dressing. Various materials like Edinburgh University's solution of lime (EUSOL), normal saline, povidone-iodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The wound healing experiments on the Albino rats showed significant variations. 27 . Honey with high osmorlarity, low pH and high peroxide content favors the outflow of fluid from wound tissue, aiding cleansing, reducing edema and decreasing pain.…”
Section: Wound Healing Potency Of Apis Honey Samples On Experimental ...mentioning
confidence: 99%
“…The wound healing experiments on the Albino rats showed significant variations. 27 . Honey with high osmorlarity, low pH and high peroxide content favors the outflow of fluid from wound tissue, aiding cleansing, reducing edema and decreasing pain.…”
Section: Wound Healing Potency Of Apis Honey Samples On Experimental ...mentioning
confidence: 99%
“…Several studies have compared between EUSOL and topical Honey for the debridement of traumatic and infected wounds 16–20 . It was observed that EUSOL‐treated surgically debrided wounds cleared of slough significantly more quickly than did those treated with topical honey, although overall healing time was significantly longer in the EUSOL‐treated control group.…”
Section: Introductionmentioning
confidence: 99%